⁶³Ni diffusion in C₆₀ fullerite - Mazanko, V.F.; Pogorelov, A.E.; Kulish, N.P.; Dmitrenko, O.P.; Lizunov, V.V. (Functional Materials, 2006)
The possibility to obtain in principle metal-fullerides using diffusion methods has been established using radioactive isotopes (⁶³Ni). The thermally activated diffusion (T = 300°C) in fullerite crystal has been assumed to occur according to the interstitial mechanism via successive filling of octa- and tetrahedral pores. The basic quantitative characteristics of diffusion in a fullerite crystal: diffusion coefficient D ~ 10⁻¹² cm²/s,β radiation absorptance in fullerite µ = 3.94*104 cm-1 and dynamics of its diffusion saturation with the metal atoms have been determined.